In vivo protein expression changes in mouse livers treated with dialyzed coffee extract as determined by IP-HPLC - Cheol Soo Yoon; Min Keun Kim; Yeon Sook Kim; Suk Keun Lee (SpringerOpen, 2018)
Abstract Background Coffee extract has been investigated by many authors, and many minor components of coffee are known, such as polyphenols, diterpenes (kahweol and cafestol), melanoidins, and trigonelline, to have anti-inflammatory, anti-oxidant, anti-angiogenic, anticancer, chemoprotective, and hepatoprotective effects. Therefore, it is necessary to know its pharmacological effect on hepatocytes which show the most active cellular regeneration in body. Methods In order to determine whether coffee extract has a beneficial effect on the liver, 20 C57BL/6J mice were intraperitoneally injected once with dialyzed coffee extract (DCE)-2.5 (equivalent to 2.5 cups of coffee a day in man), DCE-5, or DCE-10, or normal saline (control), and then followed by histological observation and IP-HPLC (immunoprecipitation high performance liquid chromatography) over 24 h. Results Mice treated with DCE-2.5 or DCE-5 showed markedly hypertrophic hepatocytes with eosinophilic cytoplasms, while those treated with DCE-10 showed slightly hypertrophic hepatocytes, which were well aligned in hepatic cords with increased sinusoidal spaces. DCE induced the upregulations of cellular proliferation, growth factor/RAS signaling, cellular protection, p53-mediated apoptosis, angiogenesis, and antioxidant and protection-related proteins, and the downregulations of NFkB signaling proteins, inflammatory proteins, and oncogenic proteins in mouse livers. These protein expression changes induced by DCE were usually limited to the range ± 10%, suggesting murine hepatocytes were safely reactive to DCE within the threshold of physiological homeostasis. DCE-2.5 and DCE-5 induced relatively mild dose-dependent changes in protein expressions for cellular regeneration and de novo angiogenesis as compared with non-treated controls, whereas DCE-10 induced fluctuations in protein expressions. Conclusion These observations suggested that DCE-2.5 and DCE-5 were safer and more beneficial to murine hepatocytes than DCE-10. It was also found that murine hepatocytes treated with DCE showed mild p53-mediated apoptosis, followed by cellular proliferation and growth devoid of fibrosis signaling (as determined by IP-HPLC), and subsequently progressed to rapid cellular regeneration and wound healing in the absence of any inflammatory reaction based on histologic observations.